Sorting on Unobserved Skills into New Firms - Polina Knutsson (Lund University, School of Economics and Management, Department of Economics, 2018)
Human capital features prominently in theoretical work on post-entry performance of new firms. Empirical analysis has, however, to a large extent overlooked the unobserved component of human capital focusing on years of education or labor market experience. This paper adds to the literature on worker characteristics and post-entry firm performance by putting the unobserved quality of workers in the center of analysis. I find strong evidence that new firms on average employ workers of lower unobserved quality relative to incumbent firms. Among new firms workers of higher unobserved quality are overrepresented in spin-offs and incorporated new firms. I further show that unobserved quality of workers is important for the post-entry performance of firms as it is a strong predictor of new firm survival.
Keywords: J24; J60; M13; 330; Human capital; occupational choice; sorting; new firms